2008
DOI: 10.3390/s8084669
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Fragments as Probe in Biosensor Development

Abstract: Today's proteomic analyses are generating increasing numbers of biomarkers, making it essential to possess highly specific probes able to recognize those targets. Antibodies are considered to be the first choice as molecular recognition units due to their target specificity and affinity, which make them excellent probes in biosensor development. However several problems such as difficult directional immobilization, unstable behavior, loss of specificity and steric hindrance, may arise from using these large mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
98
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(101 citation statements)
references
References 86 publications
0
98
0
3
Order By: Relevance
“…In view of this, various biorecognition molecules (including enzymes, Fabs, and aptamers) were earmarked for the development of SERS bionanosensors [85][86][87][88]. Efforts in this direction have led to the development of SERS bionanosensors employing antibodies for analyte recognition [89][90][91][92].…”
Section: Sers-based Immunonanosensorsmentioning
confidence: 99%
“…In view of this, various biorecognition molecules (including enzymes, Fabs, and aptamers) were earmarked for the development of SERS bionanosensors [85][86][87][88]. Efforts in this direction have led to the development of SERS bionanosensors employing antibodies for analyte recognition [89][90][91][92].…”
Section: Sers-based Immunonanosensorsmentioning
confidence: 99%
“…The use of monoclonal antibodies (mAb) may turn out to be a successful approach to obtain such a speci c response towards a selected target antigen. [28][29][30][31] This is particularly relevant when the analyte is not a single structure but a mixture of several/complex target compounds. This is the case for oxLDL, obtained by random oxidation of native LDL.…”
Section: -13mentioning
confidence: 99%
“…2,75 Through this way, the engineered camel sdAbs were immobilized for sensing human prostate-specific antigen, which demonstrated that a higher probe density mediates enhanced detection sensitivity in a surface plasmon resonance-based detection system. 75,77 This means that the use of nanobodies to generate sensitive and selective biosensors for in vitro disease diagnosis is highly feasible. 2,75 More particularly, the nanobodies have also been developed to detect disease biomarkers in human biopsies by antibody-based slide and bead arrays.…”
mentioning
confidence: 99%